2015
DOI: 10.1039/c4an01768d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient microfluidic negative enrichment of circulating tumor cells in blood using roughened PDMS

Abstract: Efficient isolation strategies not based on epithelial biomarker expression are required to enable non-biased enrichment of circulating tumor cells (CTCs). CTCs undergoing epithelial-mesenchymal transition (EMT) may be prognostically relevant, and importantly are not detected with conventional epithelial based approaches such as CellSearch®. A method for the non-biased isolation of cancer cells within a peripheral blood sample utilizing microfluidic mixing PDMS devices functionalized with anti-CD45 is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…Furthermore, a rather complete depletion of white blood cells can be achieved by the introduction of a single-step treatment of the cells with sulfuric acid, creating a certain nanoscale roughness, which results in an increased binding of CD45-positive white blood cells to CD45-conjugated surfaces. Thereby isolation and characterization of tumor cells is increased [76]. A novel EpCAM independent enrichment strategy was proposed by Schneck et al in 2015: they combined different antibodies specific for cell surface proteins and components of the extracellular matrix (ECM) components.…”
Section: New Ctc-detection Strategiesmentioning
confidence: 99%
“…Furthermore, a rather complete depletion of white blood cells can be achieved by the introduction of a single-step treatment of the cells with sulfuric acid, creating a certain nanoscale roughness, which results in an increased binding of CD45-positive white blood cells to CD45-conjugated surfaces. Thereby isolation and characterization of tumor cells is increased [76]. A novel EpCAM independent enrichment strategy was proposed by Schneck et al in 2015: they combined different antibodies specific for cell surface proteins and components of the extracellular matrix (ECM) components.…”
Section: New Ctc-detection Strategiesmentioning
confidence: 99%
“…The acidic treatment inside the PDMS channels of microfluidic chips was attempted to increase the purity of CTCs. A high‐throughput microfluidic chip with anti‐CD45 conjugated on the channel surface and roughening using Sulphur acid, achieved 99.99% WBCs capturing and 50% CTCs recovery (Diéguez, Winter, Pocock, Bremmell, & Thierry, ). Similar CTC enriching PDMS‐based membranes achieved the capture efficiency of 72.3 to 83% (Kang, Doh, & Cho, ; Zhou et al, ).…”
Section: Microfilter Structures and Fabrication Methodsmentioning
confidence: 99%
“…Track etched and cartridge filter ISET, ScreenCell (Desitter et al, 2011;Diéguez, Winter, Pocock, Bremmell, & Thierry, 2015;Fleischer, Price, & Symes, 1964;Kang, Doh, & Cho, 2015;Seal, 1964;Zhou et al, 2014) 2 Lithography CellSieve, Microfilter devices (Adams et al, 2014;Bikel et al, 2010;Chou et al, 2013;Girones et al, 2006;Mohamadi et al, 2015) 3…”
Section: Sr No Fabrication Techniquesmentioning
confidence: 99%
“…MCF7 is the most frequently used breast cancer cell line worldwide . This cell line has been used as a CTC model in studies that isolate CTC from blood cells . Moreover, numerous studies have been reported showing that red blood cells are removed from blood samples by lysis or a similar pretreatment to facilitate the separation of CTCs from blood cells .…”
Section: Introductionmentioning
confidence: 99%